2010
DOI: 10.1152/jn.00574.2010
|View full text |Cite
|
Sign up to set email alerts
|

Social and Ecological Regulation of a Decision-Making Circuit

Abstract: Ecological context, sensory inputs, and the internal physiological state are all factors that need to be integrated for an animal to make appropriate behavioral decisions. However, these factors have rarely been studied in the same system. In the African cichlid fish Astatotilapia burtoni, males alternate between two phenotypes based on position in a social hierarchy. When dominant (DOM), fish display bright body coloration and a wealth of aggressive and reproductive behavioral patterns that make them conspicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 81 publications
1
30
0
Order By: Relevance
“…Excitatory spiral fiber (SF) neurons, recently implicated in regulating M-cell firing and startle probablility (Lacoste et al, 2015) can likely be excluded on similar grounds as their input lies downstream of the M-cell soma. FF neurons, on the other hand, receive glutamatergic input from VIII afferents and are known to regulate the startle threshold in adult goldfish (Weiss et al, 2008) and African cichlid fish (Neumeister et al, 2010), and in larval zebrafish these neurons are adjacent to the M-cell lateral dendrite (Koyama et al, 2011) where their input likely influences dendritic responses. Our data are consistent with work in adult goldfish showing that inhibitory synapses on the M-cell are potentiated by repeated stimulation through a partially NMDA receptor-dependent pathway (Korn et al, 1992; Oda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Excitatory spiral fiber (SF) neurons, recently implicated in regulating M-cell firing and startle probablility (Lacoste et al, 2015) can likely be excluded on similar grounds as their input lies downstream of the M-cell soma. FF neurons, on the other hand, receive glutamatergic input from VIII afferents and are known to regulate the startle threshold in adult goldfish (Weiss et al, 2008) and African cichlid fish (Neumeister et al, 2010), and in larval zebrafish these neurons are adjacent to the M-cell lateral dendrite (Koyama et al, 2011) where their input likely influences dendritic responses. Our data are consistent with work in adult goldfish showing that inhibitory synapses on the M-cell are potentiated by repeated stimulation through a partially NMDA receptor-dependent pathway (Korn et al, 1992; Oda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the excitabilities of the Mauthner neuron in fish and the startle response that the neuron triggers both depend on the social status of the animal (Neumeister et al, 2010). Status-dependent circuit reconfiguration in other species may result from proximate mechanisms similar to those described in crayfish, including changes in modulatory function, neuronal thresholds, and the gain or sign of synaptic function (Yeh et al, 1996;Krasne et al, 1997;Herberholz et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Social status affects neurogenesis in rodents (Kozorovitskiy and Gould, 2004) and crayfish (Song et al, 2007), neuronal size in fish (White et al, 2002), brain morphology in wasps (O'Donnell et al, 2007) and naked mole rats (Holmes et al, 2007), and cell receptor populations in crayfish (Spitzer et al, 2005) and fish (Burmeister et al, 2007). Social status also affects the serotonergic neuromodulation of synaptic responses in both crayfish (Yeh et al, 1996(Yeh et al, , 1997 and fish (Whitaker et al, 2011), and the excitability of neural circuits that produce different behaviors (Krasne et al, 1997;Herberholz et al, 2001;Neumeister et al, 2010). It remains unclear, however, how neural circuits are altered to produce status-dependent behavioral responses.…”
Section: Introductionmentioning
confidence: 99%
“…A similar result has been observed in a cichlid fish where, in comparison to subordinate males, dominant males were found to display higher startle responsiveness and increased excitability of the Mauthner cell circuit that governs this behaviour. In the latter case, the difference in escape was interpreted as a trade-off between the better reproductive opportunities of being a conspicuous dominant individual and the greater predation risk that this condition represented (Neumeister et al, 2010;Whitaker et al, 2011). In both the crayfish and fish studies, however, the behavioural and neuronal differences were observed by manipulating the social status.…”
Section: Neural Response Differences Reflect the Impact Of Predationmentioning
confidence: 99%